Exploring the effects of BCG vaccination in patients diagnosed with tuberculosis: Observational study using the Enhanced Tuberculosis Surveillance system. Issue 35 (14th August 2019) - Abbott, Sam; Christensen, Hannah; Lalor, Maeve K.; Zenner, Dominik; Campbell, Colin; Ramsay, Mary E.; Brooks-Pollock, Ellen
Highlights: Found evidence of an association between BCG vaccination and reduced all-cause mortality in TB cases. Weaker evidence of an association between BCG vaccination and reduced repeat TB episodes in TB cases. There was little evidence of an association with other TB outcomes. There was weak evidence of associations between TB outcomes and age at, or years since, vaccination. Abstract: Background: Bacillus Calmette–Guérin (BCG) is one of the most widely-used vaccines worldwide. BCG primarily reduces the progression from infection to disease, however there is evidence that BCG may provide additional benefits. We aimed to investigate whether there is evidence in routinely-collected surveillance data that BCG vaccination impacts outcomes for tuberculosis (TB) cases in England. Methods: We obtained all TB notifications for 2009–2015 in England from the Enhanced Tuberculosis surveillance system. We considered five outcomes: All-cause mortality, death due to TB (in those who died), recurrent TB, pulmonary disease, and sputum smear status. We used logistic regression, with complete case analysis, to investigate each outcome with BCG vaccination, years since vaccination and age at vaccination, adjusting for potential confounders. All analyses were repeated using multiply imputed data. Results: We found evidence of an association between BCG vaccination and reduced all-cause mortality (aOR:0.76 (95%CI 0.64–0.89), P:0.001) and weak evidence of an association with reduced recurrent TB (aOR:0.90 (95%CI 0.81–1.00), P:0.056). Analyses using multiple imputation suggested that the benefits of vaccination for all-cause mortality were reduced after 10 years. Conclusions: We found that BCG vaccination was associated with reduced all-cause mortality in people with TB although this benefit was less pronounced more than 10 years after vaccination. There was weak evidence of an association with reduced recurrent TB.